Synthesis of ZnO Nanoparticle and Utilized as a Drug Carrier to Treat Leukemia - Areej Ali Jarullah; Nidhal Meteab Khamees; Taghreed Mohy Al-Deen Musa (Indonesian Journal of Chemistry, 2023)
This study includes two parts, and the first was the preparation of the Zn(II)complex by reacting N-[4-(5-{(Z)-[(5-oxo-2-sulfanyl-4,5-dihydro-1H-imidazol-1-yl)imino]methyl}furan-2-yl)phenyl]acetamide with ZnCl2. The complex was characterized by using microscopic analysis such as UV-Vis spectrum, LC-MS, FTIR spectrophotometer, measurements of conductivity, magnetic susceptibility, and atomic absorption. The second part was the preparation of the ZnO nanoparticles by dissolving the Zn(II) complex in HNO3 and HCl and its use as a drug transporter to treat leukemia. FSEM, TEM, and XRD were examined for the characterization of ZnO nanoparticles that will be used in the synthesis of most medicines and drugs in the future.